2018
DOI: 10.1021/acsnano.7b08056
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks for Cell and Virus Biology: A Perspective

Abstract: Metal-organic frameworks (MOFs) are a class of coordination polymers, consisting of metal ions or clusters linked together by chemically mutable organic groups. In contrast to zeolites and porous carbons, MOFs are constructed from a building block strategy that enables molecular level control of pore size/shape and functionality. An area of growing interest in MOF chemistry is the synthesis of MOF-based composite materials. Recent studies have shown that MOFs can be combined with biomacromolecules to generate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
179
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(194 citation statements)
references
References 128 publications
1
179
0
3
Order By: Relevance
“…Inspired by the natural sporulation process of certain bacteria and fungi strains, MOFs and MPNs have been used as new functional coatings for biological organisms to combat against physical and chemical stresses (10,11,63). Various driving forces and synthetic conditions have been exploited for growing MOFs around biological species under diverse conditions without imparting their biological functions.…”
Section: Exogenous Bioaugmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by the natural sporulation process of certain bacteria and fungi strains, MOFs and MPNs have been used as new functional coatings for biological organisms to combat against physical and chemical stresses (10,11,63). Various driving forces and synthetic conditions have been exploited for growing MOFs around biological species under diverse conditions without imparting their biological functions.…”
Section: Exogenous Bioaugmentationmentioning
confidence: 99%
“…The rapid explosion of materials research and nanotechnology in the past few decades has recently allowed us to explore alternative strategies for enhancing existing, or enabling completely new, functions within biological systems. With careful material design and construction, many synthetic materials have been successfully coupled with biological systems, demonstrating new extrinsic functional properties that surpass many existing natural capabilities of biosystems, such as the adaptation to fatal environments (9)(10)(11), the ability to prolong life cycles (12), and photosynthesis in nonphotosynthetic species (13). Biological species have gone through millions of years of evolution to achieve many of their biofunctionalities; however, given the amazing compositional and structural diversity of advanced synthetic materials, it is expected that strategies for the integration of functional synthetic materials with biological systems for the design and engineering of nanobiohybrids are a more rapid, powerful, and costeffective alternative than natural evolution or genetic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In recent years, MOFs have been integrated with metallic, ceramic, and biological moieties to form novel composite materials. [5][6][7][8] In the area of MOF bio-composites, it has been shown that MOFs can be used as carriers for therapeutics ranging from small drugs 9,10 to large biomacromolecules. 11,12 In the latter case, ZIF-8 has been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a facile release mechanism of CC‐ZIFs by the complete dissolution of the protective ZIF‐8 shell. Therefore, in terms of biocompatibility, this system is as good as the conventional ZIF‐8 biomimetic mineralization process used to grow ZIF‐8 particles on living cells or proteins …”
Section: Mof Proteinsmentioning
confidence: 77%
“…Therefore, in terms of biocompatibility, this system is as good as the conventional ZIF8 biomimetic mineralization pro cess used to grow ZIF8 particles on living cells or proteins. [68,69] There are certain formidable challenges associated with micro RNAs (miRNAs) due to their small size, easy degrada tion, and weak expression level, which lead to low sensitivity. These problems trigger the intercellular detection in cytoplasm which monitors the levels of intercellular miRNA.…”
Section: Mof Nanocarriersmentioning
confidence: 99%